The Finnmark Library: A Scholarly Library in “Ultima Thule” - Grenersen, Geir (Mémoires du livre / Studies in Book Culture)

(untitled) (Groupe de recherches et d’études sur le livre au Québec, 2022)
Finmarksbibliotheket (“The Finnmark Library”) was established in the municipality of Vadsø in 1892, by central representatives of the town. It was intended to be a systematic collection “of books and manuscripts related to the history, ethnography, language, natural history, and statistics of Finnmark County,” especially “to collect everything written about the Sámi.” Its stock increased steadily, and in 1926 the library moved into its own building. In the same period, the assimilationist (Norwegianization) policy against the Sámi and Kven (Finnish population in Norway) was in its most intense phase, and the printing of Sámi and Kven books was restricted. This article explores the paradox that a library representing a pluralistic view of language and culture was established by administrators of an assimilationist policy. What role did the library play in the Norwegianization policy? Can the profile of the book collection tell us what kind of library it was?